Social Insurance for Farmers in Poland and Lithuania - a Comparative Analysis - Astrida Miceikiene; Damian Walczak; Sylwia Pienḱowska-Kamieniecka (Comparative Economic Research. Central and Eastern Europe, 2019)
The aim of the article is to present the social insurance of farmers in Poland and Lithuania. In the study, the following research methods were used: the descriptive method, a literature review, statistical analysis, and an economic analysis of the law. On the basis of the study results, it was concluded that both countries have a different model of social insurance for farmers. This results from political decisions, but also from other aspects which have an impact on agriculture in those countries. It needs to be stressed that in Poland this type of insurance is about 90% subsidized, whereas in Lithuania this system is self-sustaining.
Keywords: H55; H61; Q10; 330; social security; pension; farmers; privileges